A functional and self-assembling octyl-phosphonium-tagged esculetin as an effective siRNA delivery agent. Issue 92 (5th November 2021) - Shaikh, Altab; Neeli, Praveen Kumar; Singuru, Gajalakshmi; Panangipalli, Sravya; Banerjee, Rajkumar; Maddi, Sridhar Reddy; Thennati, Rajamannar; Bathula, Surendar Reddy; Kotamraju, Srigiridhar
Abstract : Herein, we describe the self-assembling ability of an amphiphilic phosphonium cationic lipid to form nanoparticles and deliver MnSOD siRNA into MDA-MB-231 cells. Abstract : Herein, we document a self-assembling octyl-TPP tagged esculetin (Mito-Esc) as functionally active and as a novel small molecule siRNA delivery vector. While Mito-Esc itself induces selective breast cancer cell death, the amphiphilic nature of Mito-Esc delivers therapeutic siRNAs intracellularly without the need for any excipient to exacerbate the anti-proliferative effects.